THE FORMATION OF STUDENTS’ DISCIPLINARY BEHAVIOUR AT SMPN 1 GONDANGWETAN TOWARD DEMOTIVATING LEARNING BEHAVIOUR - Ayyukum Akhsanu Amala; Titik Indarti; Resdianto Permata Raharjo (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This article explains attitude formation programs related to students’ disciplinary behaviour at SMPN 1 Gondangwetan and the efforts made by teachers to motivate students' decreasing learning, especially for students who often violate the rules. This article aims to serve as an example for other schools to improve the quality of students’ discipline, which is followed by a decrease in their learning motivation. The approach used in this article is descriptive qualitative, which produces data in the form of words from the results of transcription and observation. The data source in the research came from students of SMPN 1 Gondangwetan, who had been grouped into several samples, along with interviews with teachers in the discipline context. The data collection techniques of the research were carried out by distributing questionnaires to students, interviewing discipline teachers, and making observations at schools. The research results indicate that there are still violations of the rules committed by students. It needs the role of parents, teachers, and students to realize their significant learning motivation.